2006
DOI: 10.3390/i7120590
|View full text |Cite
|
Sign up to set email alerts
|

Laser photolysis study of anthraquinone in binary mixtures ofionic liquid [bmim][PF6] and organic solvent

Abstract: Photochemical properties of the ionic liquid (RTIL) 1-butyl-3-methylimidazolium hexafluorophosphate [bmim] [PF 6 ] and its binary mixed solutions with organic solvent (DMF and MeCN) were investigated by laser photolysis at an excitation wavelength of 355 nm, using anthraquinone (AQ) as a probe molecule. It was indicated that the triplet excited state of AQ ( 3 AQ*) can abstract hydrogen from [bmim] [PF 6 ]. Moreover, along with the change of the ratio of RTIL and organic solvent, the reaction rate constant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Previously, we had measured the electrical conductivity of [bmim][PF 6 ]/MeCN binary mixtures and shown that the maximum conductivity of [bmim][PF 6 ]/MeCN is 37.9 mS cm -1 at V IL =0.32 . This value is consistent with the critical point (or turnover) for the k obs indicated in this work.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Previously, we had measured the electrical conductivity of [bmim][PF 6 ]/MeCN binary mixtures and shown that the maximum conductivity of [bmim][PF 6 ]/MeCN is 37.9 mS cm -1 at V IL =0.32 . This value is consistent with the critical point (or turnover) for the k obs indicated in this work.…”
Section: Resultssupporting
confidence: 90%
“…Since the absorption decays monotonically by first-order kinetics, it is concluded that the 3 DQ* decays mainly via self-quenching under a N 2 atmosphere. This observation is different from that of anthraquinone or benzophenone, whose excited states decay mainly via hydrogen abstraction of alkyl groups on the cations of [bmim][PF 6 ] under similar conditions. ,
1 (a) Transient absorption spectra of 3 DQ* recorded at 0.1 μs after 355 nm laser excitation in a IL/MeCN solution containing 1 × 10 -4 mol·dm -3 DQ under N 2 . V IL : (○) 0 and (▪) 0.8.
…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…By swelling study, in addition with several instrumental analysis, a very stable hydration structure of phenol was revealed by investigation on the ion-effect of P4VPh gel [12,14]. In these studies, p-hydrogen bond, cation-p interaction and hydrophobic interaction were found to play significant roles on phase transition of P4VPh gel in the presence of different ion species and concentrations [15][16][17][18]. However, the interactions involved with phenyl rings is still far from fully elucidated.…”
Section: Introductionmentioning
confidence: 97%